Pengaruh Media Sosial Terhadap Keputusan Pembelian Yang Dimediasi Kualitas Produk - Amalia Puspitasari; M. Syamsul Hidayat; Kasnowo Kasnowo (BISMA : Business and Management Journal, 2025)
This study examines the influence of social media on purchasing decisions with product quality as a mediating variable, focusing on consumers of Clarissa Boutique in Mojokerto, Indonesia. The scope of the study centers on digital marketing practices through Instagram and TikTok as promotional tools rather than transaction platforms, emphasizing their role in shaping consumer perceptions and behavior. Using a quantitative descriptive approach, data were collected from 200 registered customers through a structured questionnaire. The sampling technique applied was non-probability sampling with a purposive method, and the data were analyzed using Structural Equation Modeling (SEM-PLS). The findings reveal that TikTok has a strong and statistically significant effect on both product quality perception and purchasing decisions, while Instagram shows no significant influence on either variable. Furthermore, product quality does not significantly affect purchasing decisions and does not mediate the relationship between social media and purchasing decisions. These results indicate that visual and interactive content delivered through TikTok plays a more decisive role in influencing consumer purchasing behavior compared to Instagram. The study highlights the importance of selecting appropriate social media platforms in digital marketing strategies and provides practical insights for fashion retailers in optimizing social media-based promotion.